Residual Inflammatory Risk on Treatment With PCSK9 Inhibition and Statin Therapy - Pradhan, Aruna D.; Aday, Aaron W.; Rose, Lynda M.; Ridker, Paul M (Circulation (New York, N.Y.), 2018)
BACKGROUND:The combination of statin therapy and PCSK9 (proprotein convertase subtilisin/kexin type 9) inhibition markedly lowers low-density lipoprotein cholesterol (LDL-C) and reduces cardiovascular event rates. Whether residual inflammatory risk as measured by on-treatment high sensitivity C-reactive protein (hsCRP) remains an important clinical issue in such patients is uncertain. METHODS:We evaluated residual inflammatory risk among 9738 patients participating in the SPIRE-1 and SPIRE-2 cardiovascular outcomes trials (Studies of PCSK9 Inhibition and the Reduction in Vascular Events), who were receiving both statin therapy and bococizumab, according to on-treatment levels of hsCRP (hsCRPOT) and LDL-COT measured 14 weeks after drug initiation. The primary end point was nonfatal myocardial infarction, nonfatal stroke, hospitalization for unstable angina requiring urgent revascularization, or cardiovascular death. RESULTS:At 14 weeks, the mean percentage change in LDL-C among statin-treated patients who additionally received bococizumab was −60.5% (95% confidence interval [CI], −61.2 to −59.8; P<0.001; median change, −65.4%) as compared to 6.6% (95% CI, −1.0 to 14.1; P=0.09; median change, 0.0%) for hsCRP. Incidence rates for future cardiovascular events for patients treated with both statin therapy and bococizumab according to hsCRPOT <1, 1 to 3, and >3 mg/L were 1.96, 2.50, and 3.59 events per 100 person-years, respectively, corresponding to multivariable adjusted hazard ratios of 1.0, 1.16 (95% CI, 0.81–1.66), and 1.62 (95% CI, 1.14–2.30) (P-trend=0.001) after adjustment for traditional cardiovascular risk factors and LDL-COT. Comparable adjusted hazard ratios for LDL-COT (<30, 30–50, >50 mg/dL) were 1.0, 0.87, and 1.21, respectively (P-trend=0.16). Relative risk reductions with bococizumab were similar across hsCRPOT groups (P-interaction=0.87). CONCLUSIONS:In this post hoc analysis of the SPIRE trials of bococizumab in a stable outpatient population, evidence of residual inflammatory risk persisted among patients treated with both statin therapy and proprotein convertase subtilisin-kexin type 9 inhibition. CLINICAL TRIAL REGISTRATION:URLhttps://www.clinicaltrials.gov. Unique identifiersNCT01975376, NCT01975389.